Modeling and Spatial Analysis of Tourism Centers and Their Impact on Enhancing the Quality of Life in the City of Al-Khobar, Eastern Province - M. Alamri, Nourah (Journal of Posthumanism, 2025)
Modeling and spatial analysis studies of tourist centers and facilities in Al- Khobar are fundamental pillars for the future planning of this important economic sector. Saudi Arabia aims for this sector to become a major source of national income, replacing the oil sector, in line with Vision 2030. Al -Khobar, situated on the Arabian Gulf coast in the eastern Province of Saudi Arabia, is one of the cities with the potential to be a key tourist destination in the Kingdom due to its coastal location, proximity to Gulf countries, diverse tourism assets including entertainment, sports, and cultural heritage, and its distribution of tourist accommodation facilities across its various districts.Spatial analysis using Geographic Information Systems of tourist centers and facilities in Al-Khobar revealed variations in their geographical distribution, with concentration in districts close to the beach and dispersion in some inland areas. The distribution of tourist centers and facilities had an impact on quality of life indicators for residents in the city in 2024, with some of these indicators exceeding the targets set in the Quality of Life document for the Kingdom, compared to the baseline year or the 2030 target, especially in districts where tourist centers and facilities are concentrated. The spatial modeling study of tourist centers and facilities in Al-Khobar highlighted the selection of the most suitable locations for future tourism projects based on criteria such as roads, population density, slope, and proximity to the beach. It identified four categories of spatially suitable sites for these projects, ranging from areas with very high spatial suitability, accounting for 2.9% of the city’s total area, to those with low spatial suitability at 4.5%.